The Effectiveness of Ergonomic Gymnastics Against Changes in Uric Acid Levels - Jenita Laurensia Saranga'; Elmiana Bongga Linggi; Meyske Alvionita Menggasa; Peni Suddin (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Uric acid is the end product of purine metabolism, where purines are one of the components of nucleic acids found in the nucleus of body cells. Gout attacks the joints of the body and generally attacks the joints of the fingers, heels, toes, elbows, knees, and wrists. One of the treatments for high uric acid levels in the body is ergonomic exercise. Objectives: The purpose of this study was to analyze the effectiveness of ergonomic exercise on changes in uric acid levels in the community. Methods: The type of research used is Pre-Experimental with One Group Pre-Post Test Design. Sampling using the Non Probability Sampling method with the Consecutive Sampling technique with a sample of 30 respondents. This study provides an intervention for patients with gout arthritis in the form of ergonomic exercise. The implementation of the intervention begins with a Pre-Test (measurement of uric acid levels), then giving an ergonomic exercise intervention for 4 weeks (1x a week with a duration of 30 minutes), then a Post-Test (measurement of uric acid levels) is carried out. The instrument used is a multi-check uric acid measuring instrument, SOP for the implementation of ergonomic exercises, and implementation observation sheets. Results: The results of the study were that the majority of the majority age was in the late adult category (36-45 years), the majority sex was in the female sex category of 19 respondents (63.3%), and uric acid levels before being given ergonomic exercise intervention were the majority in the high category. by 28 respondents (93.3%). while the uric acid levels after the ergonomic exercise intervention were mostly in the normal category of 25 respondents (83.3%). The results of the Wilcoxon test analysis were obtained (p = 0.000 = 0.05) where ergonomic exercise was effective in reducing uric acid levels. Conclusion: The results of this study indicate that there is a significant effect of ergonomic exercise on reducing people's uric acid levels, so the researchers recommend to the community, especially gout arthritis sufferers, to make ergonomic exercise interventions one of the intervention options that can be done independently, practically and efficiently in reducing levels. gout and the need for attention to the regulation of a healthy lifestyle to prevent more severe complications in the future.